GREEN ADOPTION AND ORGANIZATION PERFORMANCE: ASSESSING THE EFFECT OF ENVIRONMENTAL PROACTIVITY (IITM Journal of Business Studies, 2024)
Since the Industrial Revolution, human  economic activities have added a huge amount of  Greenhouse Gases (GHGs) into the environment.  The rise in environmental pollution, the global  average temperature, and sea level now present an  alarming situation all over the world, requiring  action by all concerned. It is in this regard that  the present work has been undertaken with a  focus on identifying and examining the drivers  for their influence on organizations’ green  adoption and sustainable performance. Through  random sampling, primary responses were  obtained from the managers of 103 organizations  based in India. The use of step-wise regression  analysis on cross-sectional data yielded findings  that establish a significant impact of three out of  five drivers, namely organization characteristics,  public policy, and technology characteristics,  on green adoption by organizations. The results  also support a positive and significant impact of  green adoption on economic, social, as well as  environmental performance of organizations.  The practical suggestions outlined in the study  can be used by organizations to adopt and  promote green programs as a profitable endeavor  for their sustainable growth in the future.
Keywords: Environment Deterioration; Green Adoption; Organizations; Green Strategies; Sustainable Performance